Pengembangan Model Pembelajaran Gerak Dasar untuk Siswa Sekolah Dasar - Apriyadi Aprriyadi; Jujur Gunawan Manullang; ⁠Farizal Imansyah; ⁠Grace Kharisma Tambunan (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aims to develop a game-based model for teaching basic movement skills to primary school pupils and to test its validity and practicality in Physical Education (PE). This model was developed based on motor development theory and the framework of basic movement skills, as well as an analysis of the learning conditions required for PE at the research site. Materials and methods. The research method employed was Research and Development (R&D) using the ADDIE approach, which comprises the stages of analysis, design, development, implementation, and evaluation. The research subjects were 20 Year 1 and Year 2 primary school pupils aged 6–8 years at SD Negeri 18 Talang Kelapa, Banyuasin Regency. The model developed consists of 10 play activities integrating four basic movement components: walking, running, jumping, and throwing, designed to be contextual and appropriate to the physical and cognitive characteristics of early primary school pupils. Data collection was carried out using an expert validation questionnaire and a student practicality questionnaire, which were analysed using descriptive statistics with percentage calculations. Results. The research results indicate that the developed learning model achieved a validity score of 86.80% (valid category), assessed by a learning expert, a media expert, and a physical education practitioner, as well as a practicality score of 87.40% (practical category) based on a student field trial. These findings confirm that the game-based basic movement learning model is suitable and easy to implement in physical education at primary schools. Conclusion. The conclusion of this study is that the developed game-based basic movement learning model is valid and practical and can serve as an innovative alternative learning model to improve basic movement skills in early-age primary school pupils.